Regulatory role, clean logistics technology and environmental sustainability - Maji, Ibrahim Kabiru; Saari, Mohd Yusof; Muhammad, Shuaibu (Elsevier, 2024)
This study examines the pivotal role that regulatory frameworks play in driving the adoption of clean logistics technologies and ensuring friendly environment in Bauchi. A 5-point Likert scale instrument was used to collect data from the recruited respondents along with stratified snowball sampling method. Important variable indicators of regulatory role, clean logistics technology and environmental pollution were visualized using charts while regression was used for inferential analysis. The results reveled a positive link between regulatory role and clean logistics technology. Suggesting that an increase in regulatory role by 1 will increases clean logistics technology, specifically, the use of alternative energies by 0.2. Moreover, the result shows a negative and important association between government regulatory role and environmental pollution. This implies that an increase in government regulatory role by 1 will mitigate environmental pollution by 0.1. Furthermore, the result reveals a negative relationship between clean logistics technology and environmental pollution. Thus, a 1 increase in clean logistics technology will reduce environmental pollution by 0.1. The implications of these findings for policy purpose are: (i) improved regulatory role is required to facilitate the adoption of clean logistics technology and achieve sustainable environment; (ii) minimizing emissions by logistics operators through adopting alternative sources of energy will further improve environmental sustainability.